Perencanaan Infrastruktur Teknologi Informasi pada Bank dengan Framework TOGAF - Ekawati, Rika Kharlina (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
Implementation of information technology is intended to achieve business process alignment, especially in the field of banking. Some of the obstacles faced by banks include system of services transaction processing and data access. Lack of awareness in infrastructure planning results in company losses and inappropriately targeted use. The aim of the research is is to plan the information technology infrastructure and simplify the existing system in Bank, with case study at one of national private bank. The research use the organization's information technology architecture planning methodology based on the concept of information technology solutions that have been mapped and implementing the TOGAF framework, The proposed system to support the development of implementation strategies as a foundation for information technology architecture. The results of gap analysis show that there are several applications that must be developed to connect the management and customers and to manage transaction data and customer data. It also needs to develop mobile banking to maximize the 24-hour service. From this planning is expected to improve the performance of bank service and implement the right information technology system to support the smoothness of business process.